Analysis of thermal stratification phenomena in the CIRCE-HERO facility. (15th June 2020) - Buzzi, F.; Pucciarelli, A.; Galleni, F.; Tarantino, M.; Forgione, N.
Highlights: CFD calculations of LBE Thermal-Hydraulics in in a pool vessel are performed. Measured and calculated temperature trends are compared for four operating conditions. Sensitivity analyses about the influence of the inlet velocity distribution were performed. Abstract: In the present paper, CFD simulations related to the operating conditions considered during the experimental campaign on CIRCE-HERO facility are presented, with the aim of investigating the observed temperature stratification phenomena. Calculations are performed using the commercial codes STAR-CCM+ and ANSYS Fluent adopting a RANS approach; the numerical results and the experimental data are compared. Four distinct experimental tests are investigated also performing sensitivity analyses regarding the boundary conditions. In particular, assumptions concerning the heat losses distribution and the shape of the pool inlet were taken into account. The numerical results provide support for further understanding of the involved phenomena, suggesting the possible causes of the thermal stratification observed experimentally inside the pool. Similar trends for the predicted and experimental data were obtained and – even from a quantitative point of view - the observed discrepancies can be considered acceptable, assuming the uncertainties in the experimental boundary conditions and measurement.